How far are the new wave of mRNA drugs from us? mRNA product current perspective and future development - Duan, Qiongyu; Hu, Tianyu; Zhu, Qiuxia; Jin, Xueying; Chi, Feng; Chen, Xiaodong (Frontiers in Immunology, 2022)
mRNA products are therapies that are regulated from the post-transcriptional, pre-translational stage of a gene and act upstream of protein synthesis. Compared with traditional small molecule drugs and antibody drugs, mRNA drugs have the advantages of simple design, short development cycle, strong target specificity, wide therapeutic field, and long-lasting effect. mRNA drugs are now widely used in the treatment of genetic diseases, tumors, and viral infections, and are expected to become the third major class of drugs after small molecule drugs and antibody drugs. The delivery system technology is the key to ensuring the efficacy and safety of mRNA drugs, which plays an important role in protecting RNA structure, enhancing targeting ability, reducing the dose of drug delivery, and reducing toxic side effects. Lipid nanoparticles (LNP) are the most common delivery system for mRNA drugs. In recent years, mRNA drugs have seen rapid development, with the number of drugs on the market increasing each year. The success of commercializing mRNA vaccines has driven a wave of nucleic acid drug development. mRNA drugs are clinically used in genetic diseases, oncology, and infectious diseases worldwide, while domestic mRNA clinical development is focused on COVID-19 vaccines, with more scope for future indication expansion.